SARS-CoV-2 infection risk among vaccinated and unvaccinated household members during the Alpha variant surge – Denver, Colorado, and San Diego, California, January–April 2021. Issue 33 (5th August 2022) - McCormick, David W.; Konkle, Stacey L.; Magleby, Reed; Chakrabarti, Ayan K.; Cherney, Blake; Lindell, Kristine; Namageyo-Funa, Apophia; Visser, Susanna; Soto, Raymond A.; Donnelly, Marisa A.P.; Stringer, Ginger; Austin, Brett; et al.
Highlights: Vaccination reduces the risk household transmission of SARS-CoV-2. Fewer households with a fully vaccinated primary case had secondary cases. The primary SARS-CoV-2 variant in this investigation was the Alpha variant. Vaccinated secondary cases reported fewer symptoms than unvaccinated secondary cases. Abstract: Background: COVID-19 vaccination reduces SARS-CoV-2 infection and transmission. However, evidence is emerging on the degree of protection across variants and in high-transmission settings. To better understand the protection afforded by vaccination specifically in a high-transmission setting, we examined household transmission of SARS-CoV-2 during a period of high community incidence with predominant SARS-CoV-2 B.1.1.7 (Alpha) variant, among vaccinated and unvaccinated contacts. Methods: We conducted a household transmission investigation in San Diego County, California, and Denver, Colorado, during January-April 2021. Households were enrolled if they had at least one person with documented SARS-CoV-2 infection. We collected nasopharyngeal swabs, blood, demographic information, and vaccination history from all consenting household members. We compared infection risks (IRs), RT-PCR cycle threshold values, SARS-CoV-2 culture results, and antibody statuses among vaccinated and unvaccinated household contacts. Results: We enrolled 493 individuals from 138 households. The SARS-CoV-2 variant was identified from 121/138 households (88%). The most common variants were Alpha (75/121, 62%) and Epsilon (19/121, 16%). There were no households with discordant lineages among household members. One fully vaccinated secondary case was symptomatic (13%); the other 5 were asymptomatic (87%). Among unvaccinated secondary cases, 105/108 (97%) were symptomatic. Among 127 households with a single primary case, the IR for household contacts was 45% (146/322; 95% Confidence Interval [CI] 40–51%). The observed IR was higher in unvaccinated (130/257, 49%, 95% CI 45–57%) than fully vaccinated contacts (6/26, 23%, 95% CI 11–42%). A lower proportion of households with a fully vaccinated primary case had secondary cases (1/5, 20%) than households with an unvaccinated primary case (66/108, 62%). Conclusions: Although SARS-CoV-2 infections in vaccinated household contacts were reported in this high transmission setting, full vaccination protected against SARS-CoV-2 infection. These findings further support the protective effect of COVID-19 vaccination and highlight the need for ongoing vaccination among eligible persons.